Pengaruh Postingan Instagram @Lambe_Turah Terhadap Kesiapan Untuk Menikah (Studi Kasus Perceraian Baim Wong dan Paula Verhoeven ) - Al Fauziah, Saidatul Aminah; Budhiharti, Widya; Rahman, Khairul Arief (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The declining number of marriages in Indonesia has become a noteworthy social phenomenon, particularly in relation to the influence of social media platforms such as Instagram. The @lambe_turah account, which has over 12 million followers, reflects a strong public interest in its content. This study aims to examine the influence of Instagram, specifically the @lambe_turah account, on individuals' readiness for marriage, focusing on three subvariables: intensity of exposure, message content, and attractiveness of the content. The study population consisted of @lambe_turah Instagram followers, with a sample of 100 respondents determined using the Slovin formula. This research employed a quantitative descriptive method, utilizing questionnaires as the primary data collection instrument. The findings indicate that all three subvariables significantly influence marital readiness, as evidenced by t-values exceeding the critical threshold. Collectively, the three variables accounted for 44.2% of the variation in marital readiness, while the remaining 55.8% was attributed to other factors beyond the scope of this study. The results suggest that frequent exposure to content, the thematic focus on celebrity marital issues, and the appeal of content presentation play a notable role in shaping individuals’ perceptions and attitudes toward marriage